(untitled) (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY Despite the high prevalence of multimorbidity, we lack detailed descriptive data on the most prevalent combinations of chronic comorbidities in Switzerland. We aimed to describe and quantify the most prevalent combinations of comorbidities in internal medicine multimorbid inpatients. METHODS We conducted a multicentre retrospective cohort study including all consecutive adults (n = 42,739) discharged from the general internal medicine department of three Swiss tertiary teaching hospitals in 2010–2011. We used the Chronic Condition Indicator and the Clinical Classification Software to classify International Classification of Diseases diagnosis codes into chronic or acute diseases, into body system categories and into categories of chronic comorbidities. We defined multimorbidity as ≥2 chronic diseases. We described the most prevalent combinations of comorbidities and their prevalence. RESULTS Seventy-nine percent (n = 33,871) of the patients were multimorbid, with a median of four chronic diseases. Chronic heart disease, chronic kidney disease, solid malignancy and substance-related disorders were the most prevalent comorbidities, with a prevalence of more than 10% for each. All these comorbidities were frequently found in combination with chronic obstructive pulmonary disease and bronchiectasis, pulmonary heart disease, and peripheral and visceral atherosclerosis. Chronic heart disease was identified in 80% of the most prevalent combinations. Half of the combinations occurred more often than it would have been expected if they were independent. CONCLUSIONS The vast majority of patients fulfilled the criteria for multimorbidity. Chronic heart disease, chronic kidney disease, solid malignancy and substance-related disorders were each present in at least one tenth of the patients. This in-depth description of the most frequent comorbidities and of their frequent associations in a multicentre population may advise healthcare providers to improve preventive care and develop appropriate guidelines for multimorbid patients.